2013
DOI: 10.1093/ejcts/ezt127
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of fenestrated stent grafts for thoracic aortic aneurysms

Abstract: Treatment with fenestrated SGs does not require surgical transposition of the arch branches. The procedure is widely applicable and less invasive and outcomes are excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The site of the entry tear and the extent of dissection were determined on 0.5-to 1-mm preoperative CT slices, including arterial-and venous-phase images. Three types of nonfenestrated thoracic stent-graft, including the Relay (Bolton Medical SL, Barcelona, Spain), GORE TAG (WL Gore & Associates, Inc, Flagstaff, Ariz), and Zenith Tx2 (Cook Medical Inc, Bloomington, Ind), and 1 fenestrated thoracic stent-graft (Najuta, Kawasumi Laboratory, Tokyo, Japan) 17,18 were used. Covered length was determined intraoperatively according to the aortic pathology.…”
Section: Endovascular Treatment Between March 2009 and May 2013 123mentioning
confidence: 99%
“…The site of the entry tear and the extent of dissection were determined on 0.5-to 1-mm preoperative CT slices, including arterial-and venous-phase images. Three types of nonfenestrated thoracic stent-graft, including the Relay (Bolton Medical SL, Barcelona, Spain), GORE TAG (WL Gore & Associates, Inc, Flagstaff, Ariz), and Zenith Tx2 (Cook Medical Inc, Bloomington, Ind), and 1 fenestrated thoracic stent-graft (Najuta, Kawasumi Laboratory, Tokyo, Japan) 17,18 were used. Covered length was determined intraoperatively according to the aortic pathology.…”
Section: Endovascular Treatment Between March 2009 and May 2013 123mentioning
confidence: 99%
“…In most series, it has been reported that the need for many unplanned adjunctive intraoperative procedures to achieve an optimal outcome is common but also access related complications. The technique has also expanded to thoracic cases (Mc Williams et al 2004, Yuri et al 2013. Small series of using this technique in thoracic aorta allows preserving aortic branch flow to vital side branches.…”
mentioning
confidence: 99%
“…20 Excellent results with custom-made fenestrated devices have been reported. [21][22][23] The Japanese Najuta fenestrated thoracic stent graft (Kawasumi Laboratories, Tokyo, Japan) uses a combination of preformed stainless steel stents, externally attached PTFE, and curved delivery sheaths for total endovascular aortic arch reconstruction. In a study of the first-generation thoracic stent graft in more than 380 patients, technical success was achieved in 95.8% of patients, with a perioperative mortality rate of 1.6%, paraplegia rate of 0.8%, and CVA rate of 1.8%.…”
Section: Total Endovascular Arch Reconstructionmentioning
confidence: 99%
“…In a study of the first-generation thoracic stent graft in more than 380 patients, technical success was achieved in 95.8% of patients, with a perioperative mortality rate of 1.6%, paraplegia rate of 0.8%, and CVA rate of 1.8%. 22 In a more recent experience, the authors successfully deployed the fenestrated arch device in more than 99% of the 393 patients, with a perioperative mortality rate of 1.5%, stroke rate of 1.7%, and paraplegia rate below 1%. 24 These studies confirm the excellent early results with fenestrated grafts.…”
Section: Total Endovascular Arch Reconstructionmentioning
confidence: 99%